Demand for additional foreign language activities in Poland - Małgorzata Kłobuszewska (Central European Economic Journal (CEEJ), 2022)
This paper addresses the issue of participation in additional activities in foreign languages among Polish students aged 7-15. Foreign language skills are important in recruitment to secondary school and university. In the labour market, there is also a considerable wage premium for foreign language skills. Participation in such activities is therefore a form of investment in human capital. In this work we distinguish two kinds of additional foreign language activities: paid and free, and we show their different characteristics, which is our contribution to the literature. We check whether the key factors on the demand and supply side of additional activities such as family socio-economic status (SES) and size of the place of residence affect the participation in paid and free activities in a similar way. We also examine gender differences in additional foreign language activities participation. For the purpose of our analysis, we use data from the second round of the Determinants of Educational Decisions study (UDE) and apply the multinomial logit regression model. Our results indicate that family SES and size of the place of residence are important factors for probability of participation in paid foreign language activities. For participation in free activities, family SES does not matter. Therefore, these classes can contribute to equalising educational opportunities. We also find that girls are more likely to participate in both paid and free activities in foreign languages.
Keywords: I20; I24; J16; 330; additional activities; family SES; foreign language activities; gender; multinomial logit